A survey on investment efficiency-oriented power grid infrastructure planning - Wu, Qiang; Zhou, Ming; Yan, Jiong; Sang, Zixia; Wang, Sicong (Frontiers in Energy Research, 2025)
This paper proposes an investment efficiency-oriented strategy for power grid infrastructure planning with high penetration of renewable energy sources. First, a multi-objective investment portfolio optimization model based on data envelopment analysis is proposed to improve the cost efficiency of power grid infrastructure planning. Then, an evolutionary algorithm based on super-efficiency hyperplane projection transformation is developed to obtain the optimal Pareto frontier of the multi-objective investment portfolio. Furthermore, a super-efficiency envelope model with non-radial relaxation variables is formulated to identify an optimal investment efficiency-oriented solution from the Pareto frontier set. Comparative case studies have been implemented to demonstrate the superior performance of the proposed strategy for investment efficiency enhancement of power grid infrastructure planning.